Normal Variant Occipital Pneumatization. Issue 9 (October 2018) - Tomblinson, Courtney M.; Deep, Nicholas L.; Fletcher, Geoffrey P.; Nelson, Kent D.; Patel, Ameet C.; Weindling, Steven M.; Lane, John I.; Hoxworth, Joseph M.
Abstract : Objective: Evaluate prevalence and pattern of occipital pneumatization (OP). Patients: Individuals with imaging evidence of OP on computed tomography (CT). Intervention(s): High resolution CT scans of the temporal bone. Main Outcome Measure: The prevalence and pattern of OP on 1000 CT scans performed at a large academic healthcare system. Results: OP had a prevalence of 11.8% (n = 118) while occipital condyle pneumatization occurred in only 0.3%. Occipital air cells were right-sided in 27.1% (n = 32), left-sided in 51.7% (n = 61), and bilateral in 21.2% (n = 25), and OP was contiguous with the occipitomastoid suture. In cases of unilateral OP, the contralateral jugular foramen demonstrated relative enlargement ( p  = 0.006), but a direct association could not be established. Conclusions: The occipital bone is an accessory site of skull base pneumatization in 11.8% of the population undergoing temporal bone CT, while air cell extension into the occipital condyle occurs more rarely. These occipital air cells have a left-sided predilection and are always in direct proximity to the occipitomastoid suture, suggesting developmental egress from the mastoid. OP is a normal variant and lacks features of craniocervical pneumatization, which is a rare disorder.